Quality Assessment of Construction Schedules - Roman Marcinkowski (Communications - Scientific letters of the University of Zilina, 2003)
Preparing a schedule is a creative activity. Depending on the planner’s imagination and inventiveness different visions of the plan of the same project are created. At this stage it is worth asking which plan is the best, with which scenario for the works execution the effect of the contractor’s construction operation is the most desirable. This article presents a formalized method of construction schedules’ quality assessment. Its methodical basis is constituted by the model of production scheduling process in a construction execution unit. The assessment of schedules is referred to the absolute scale (in interval 0,1) and is objectified using the costs of realization means outage.